Performance comparison of CPLD and PLD based traffic light control system - Asad, Ishtaque; Asaduzzaman, Md.; Sobhan, Tanvir; Morshed, Khandaker Mohd. Sabbir (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.